2017
DOI: 10.3390/molecules22040613
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrrolo[1,2-a]pyrimidine Enantiomers via Domino Ring-Closure followed by Retro Diels-Alder Protocol

Abstract: From 2-aminonorbornene hydroxamic acids, a simple and efficient method for the preparation of pyrrolo[1,2-a]pyrimidine enantiomers is reported. The synthesis is based on domino ring-closure followed by microwave-induced retro Diels-Alder (RDA) protocols, where the chirality of the desired products is transferred from norbornene derivatives. The stereochemistry of the synthesized compounds was proven by X-ray crystallography. The absolute configuration of the product is determined by the configuration of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The reaction of propargylamides 5 and 14 with 2-formylbenzoic acid is plausibly interpreted as a domino process, in which the first step is the Schiff base formation [ 47 , 50 ]. The Schiff base undergoes ring closure to give isoindolo[2,1- a ]quinazolinones 6 and 15, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of propargylamides 5 and 14 with 2-formylbenzoic acid is plausibly interpreted as a domino process, in which the first step is the Schiff base formation [ 47 , 50 ]. The Schiff base undergoes ring closure to give isoindolo[2,1- a ]quinazolinones 6 and 15, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The skeletal transformations of heterocycles take its place in the construction of complex molecular frameworks from simple feedstock among the most powerful synthetic strategies [ 43 , 44 , 45 ]. Within this context, domino ring closure and RDA are the predominant approaches, since they lead to valuable nitrogenated heterocycles of high biological activity [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], such as isoindolo- and pyrroloquinazolinones. In our laboratory, their reactivity and skeletal deformation have been widely examined under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The latter heterocyclic core has not yet been explored in depth by modifying the π-system with different substituents. 6 Some methodologies have been reported that are based on a 2-aminopyrrole and 1,3-dicarbonylic system, as described by Grinev et al, 8 Bao et al, 7 and Huang et al 9 Gevorgyan et al 10 studied the synthesis with 2-alkynylpyrimidine. Another approach is the use of Fischer carbene complexes (FCCs) for the synthesis of carbo-and heterocycles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The starting chiral substrates are frequently obtained from the chiral pool. Fekete et al show in their research article how enantiomeric bicyclic pyrrolo-pyrimidines can be obtained by transferring the chirality from norbornene derivatives using a domino ring-closure protocol [ 2 ]. In this case, both enantiomers of the initial norbornene derivatives were obtained by the old but reliable resolution of a racemate.…”
mentioning
confidence: 99%